Preparation of a Composite Material from Palm Oil Fiber and an Ecological Emulsion of Expanded Polystyrene Post-Consumption - Gutiérrez-Estupiñán, Cindy; Gutiérrez-Gallego, José; Sánchez-Soledad, Melba (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The overproduction of plastics and the wide availability of natural fibers that become a source of contamination before ending their useful life, in a context of environmental crisis, has led researchers to study how to integrate them into the production of biocomposites. For this project, the development of a composite material that integrated expanded post-consumer polystyrene (EPS) and palm fiber (OPEFB) was proposed. OPEFB fibers were obtained from palm growers in the region, being processed by drying, grinding and sieving with a particle size (Mesh of 30,40, 50, 60 and 70). To obtain the solvent of the EPS, a volume of orange essential oil (Citrus sinensis) was distilled off by steam and the amount of d-limonene present was quantified using the gas chromatography technique coupled to mass spectrometry. Subsequently, the EPS was dissolved and a solubility of 0.5 g / mL was reached and with this volume a 1: 2 water / EPS-Citrus Sinensis emulsion was formulated which was characterized using the optical microscopy technique and two dyes of different polarity to observe its affinity with both phases, allowing it to be classified as a W/O type macroemulsion. The agglomerates were made by a process of molding, pressing and heating for baking. All the above parameters were kept constant and only the fiber size varied. The tests of resistance to compression and hardness showed that, to a smaller fiber size, less hardness, resistance to compression and stiffness, so the specimens made with mesh fibers (Mesh) No. 40 showed better performance in mechanical tests.